THE EFFECT OF SALES GROWTH AND PROFITABILITY ON STOCK PRICES VIA CAPITAL STRUCTURE - Suo, Abd Haris; Zainuddin, Fatlina; Fattah, Vitayanti (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2025)
This study analyzes the impact of revenue growth and profitability on stock prices, focusing on capital structure as an intermediary variable in the property sector listed on the Indonesia Stock Exchange. The research adopts a quantitative approach, using secondary data from observations and official records of the Indonesian Stock Exchange. The data span 2020-2023 and comprise a sample of 21 companies selected through purposive sampling. Data analysis was conducted using path analysis in AMOS 26. The findings indicate that revenue growth has a positive but statistically insignificant effect on both capital structure and stock prices. In contrast, profitability has a negative yet statistically significant effect on capital structure, while it has a positive and meaningful influence on stock prices. Capital structure, however, shows a negative but statistically insignificant impact on stock prices. Thus, capital structure does not mediate the relationship between revenue growth, profitability, and stock prices.